Integrasi Pengembangan Nilai Agama dan Moral Serta Sosial-Emosional Anak Usia Dini - Sari, Santi Kartika (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2025)
The development of early childhoods’ religious and moral values, as well as social-emotional values ​​become the fundamental aspects in the form of early childhoods’ personality and character which is the basis to them for further growth and development. This study aims to identify the concept of early childhood, the concept of developing religious and moral values ​​of early childhood, and the concept of social-emotional development of early childhood. In this study, the researcher used the qualitative method under a literature review approach (library research). The results of this study show that early childhood is a child with the age range of 0-6 years, which requires optimal stimulation through early childhood education (ECE). ECE focuses on the process of learning while playing to develop early childhoods’ potentions holistically. Based on Oser and Kohlberg's Theories, the development of early childhoods’ religious and moral values ​​is greatly influenced by real experiences, parental habits, and cognitive development. The whole of them are required the encouragement and guidance from adults. In line with the early childhood social-emotional development, it is formed through appropriate stimulation and guidance from family, teachers and the environment. Furthermore, Vygotsky and Piaget emphasized that social interaction and internalization of language are very important to be accustomed from an early age since from the family environment which functions to form self-control, empathy, and positive interaction skills. Therefore, this study attempts to fill the literature gap by highlighting a conceptual study that explicitly integrates the concept of early childhood, the concept of developing relevant religious and moral values ​​in early childhood, and the concept of comprehensive social-emotional development in early childhood, as a systematic theoretical foundation for designing holistic ECE programs.